2014
DOI: 10.1093/ndt/gfu334
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin use, mortality, bleeding and stroke in haemodialysis patients with atrial fibrillation

Abstract: In our population of HD patients with AF, the mortality is very high. OAT is not associated with increased mortality, while antiplatelet drugs are. OAT seems, on the contrary, associated with a better survival; however, it does not decrease the incidence of ischaemic stroke, whereas it increases the incidence of bleeding. Bleeding risk is lower in subjects in whom the INR is kept within the therapeutic range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 26 publications
(40 reference statements)
5
108
2
1
Order By: Relevance
“…161 Such concerns are particularly relevant because observational studies have shown no association between warfarin use and averted stroke in patients with severe CKD. 160,[162][163][164] Available data suggest that the efficacy of rivaroxaban, dabigatran, apixaban, and edoxaban is comparable to that of warfarin and that they can be safely used in people with stage 3 CKD. Rivaroxaban, dabigatran, and apixaban are approved for use in the United States in people with stage 4 CKD, and apixaban is approved for use in dialysis patients, all on the basis of pharmacokinetic data without any evidence of clinical efficacy or safety.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…161 Such concerns are particularly relevant because observational studies have shown no association between warfarin use and averted stroke in patients with severe CKD. 160,[162][163][164] Available data suggest that the efficacy of rivaroxaban, dabigatran, apixaban, and edoxaban is comparable to that of warfarin and that they can be safely used in people with stage 3 CKD. Rivaroxaban, dabigatran, and apixaban are approved for use in the United States in people with stage 4 CKD, and apixaban is approved for use in dialysis patients, all on the basis of pharmacokinetic data without any evidence of clinical efficacy or safety.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…However, differences in study design might also play a significant role. Previous studies enrolled incident HD patients [14][15][16]23] who have higher mortality rates in the first weeks of treatment, screened for eligibility only those hospitalized for a cardiac event [17], and enrolled patients with pre-existing AF [16,22] , two potential sources of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…This turns into a low prevalence of warfarin prescription (less than 50% of the patients) [27]. In this specific setting characterized by a very high mortality, anticoagulation seems to be associated with a better survival; furthermore, patients with the highest time of International Normalized Ratio (INR) in therapeutic range had the lowest bleeding rate [28].…”
Section: Estimation Of Renal Functionmentioning
confidence: 99%